Bioactive, antioxidant and antimicrobial properties of chemically fingerprinted essential oils extracted from Eucalyptus globulus: in-vitro and in-silico investigations - Nasir Shah, Said; Khan, Ibrar; Tul Muntaha, Sidra; Hayat, Azam; Ur Rehman, Mujaddad; Ali Shah, Tawaf; Siddique, Farhan; Salamatullah, Ahmad Mohammad; Mekonnen, Amare Bitew; Bourhia, Mohammed (Frontiers in Chemistry, 2023)
Innovative approaches are urgently required to treat divestating bacterial diseases in the face of rising bacterial resistance rates. The current investigative work focused on hydro-distilling Tasmanian blue gum (Eucalyptus globulus) to isolate the essential oil, which was then tested for bioactivity, antioxidant capacity, and antibacterial activity using in-vitro and in silico assays. The antioxidant activity was avualated against DPPH and FRAP. With results of 69.63 RSA (%) (µL/L AAE) at a concentration of 5 mL/L and 51.56 (µL/L AAE) at concentration of 90 ppm in the 2,20-diphenyl-1-picryl hydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays, respectively, the extracted oil indicated considerable antioxidant activity. The extracted oil demonstrated powerful antibacterial activity in in-vitro tests against both Gram-positive and Gram-negative bacterial strains, including Bordetella bronchiseptica (21 mm), Staphylococcus epidermidis (19 mm), and Staphylococcus aureus (19 mm), with significant minimal inhibitory (MIC) and minimum bactericidal (MIB) concentrations. Additionally, GC-MS analysis of the oil from E. globulus identified several low-molecular-weight compounds, including Eucalyptol, γ-Terpinene, Shisool acetate, 1,3-trans,5-cis-Octatriene, 2,6-Dimethyl-1,3,5,7-octatetraene, E,E, Cyclohexene, 1-methyl-4-(1-methylethylidene), Benzene, 1-methyl-4-(1-methylethenyl), Butanoic acid, 3-methyl-, 3-methylbutyl ester, and 1,3,8-p-Menthatriene. Several other compounds were also identified, including Fenchol, 2-Methyl-trans-3a,4,7,7a-tetrahydroindane, (E,E,E)-2,4,6-Octatriene, 1,2,3,6-Tetrahydrobenzylalcohol, acetate, Alloaromadendrene, Phenol, 2-ethyl-4,5-dimethyl, Phenol, 2-methyl-5-(1-methylethyl)-, p-Cymen-7-ol, 1,5,5-Trimethyl-6-methylene-cyclohexene, 1,3-Cyclohexadiene, 1-methyl-4-(1-methylethyl)-, 2,6-Octadien-1-ol, 3,7-dimethyl-, acetate, (Z), and more. The bioactive potential of Eucalyptus globulus essential oil against 1AJ6 and 1R4U was highlighted by molecular docking analyses, suggesting its utility as a natural source of antioxidant and antibacterial compounds with the potential to replace chemical disinfectants in a variety of applications.